Ideología y psicología - Luzoro, Jorge (Revista Chilena de Humanidades, 2016)
Jorge Luzoro inquires into the significance of different elements of the problematics of modern science, as constituting fundamental ideas which could contribute to valid formulations. In the particular sphere of psychology, the author indicates stages, thoughts and thinkers relevant to a scientific elaboration of this discipline.